Sociodemographic disparities in chemotherapy treatment and impact on survival among patients with metastatic bladder cancer - Klapheke, Amy (Urol Oncol, 2018)
OBJECTIVE: To evaluate how socioeconomic status and other demographic factors are associated with the receipt of chemotherapy and subsequent survival in patients diagnosed with metastatic bladder cancer. METHODS: Using data from the California Cancer Registry, we identified 3,667 patients diagnosed with metastatic urothelial carcinoma of the urinary bladder between 1988 and 2014. The characteristics of patients who did and did not receive chemotherapy as part of the first course of treatment were compared using chi-square tests. Logistic regression was used to identify predictors of chemotherapy treatment. Fine and Gray competing-risks regression and Cox proportional hazards regression were used to estimate bladder cancer-specific and all-cause mortality, respectively. RESULTS: Less than half (46.3%) of patients received chemotherapy. Patients from the lowest socioeconomic quintile were half as likely to have chemotherapy as those from highest quintile (OR = 0.5, 95% CI: 0.4, 0.7). Unmarried patients were significantly less likely to receive treatment (OR = 0.6, 95% CI: 0.5, 0.7). Not receiving chemotherapy was associated with greater mortality from bladder cancer (sHR = 1.4, 95% CI: 1.3, 1.5) and from all causes (HR = 2.0, 95% CI: 1.8, 2.1). CONCLUSIONS: We found clear disparities in chemotherapy treatment and survival with respect to socioeconomic and marital status. Future studies should explore the possible reasons why patients with low socioeconomic status and who are unmarried are less likely to have chemotherapy.